Synthesis and Characterisation of Cerium-Exchanged Zeolites and Its Application in the Removal of Arsenic from Wastewater Samples - Ab Rahim, Farha (2008)
Zolite P was synthesized from silica of rice husk ash (SRHA) via alkaline hydrothermal technique with sodium aluminate and sodium hydroxide. The zeolite produced was characterized by X-ray diffraction (XRD) and Fourier Transform Infrared Spectroscopy (FTIR) and, the morphology was analysed by Scanning Electron Microscopy (SEM), and the elemental analysis was carried out by Energy Dispersive X-ray (EDX) and inductively coupled plasma-atomic emission spectrometry (ICP-AES). The synthesized zeolite P was exchanged with cerium (III) and cerium (IV) ions. The ability of Ce(III) exchanged zeolite P (Ce3ZP) and Ce(IV) exchanged zeolite P (Ce4ZP) to sorb and remove arsenic (V) from aqueous solution was investigated. Parameters investigated for arsenic removal include pH, initial As(V) concentration, temperature and effect of foreign ions on the sorption. The sorbent was tested for removal of arsenic from industrial wastewater samples of wood treatment industry which utilized the largest amount of arsenic compound. The XRD pattern shows that the zeolite produced was zeolite P which has GIS frame work topology of type NaP1. The XRD intensity of zeolite P increases for increased ratio of SRHA:Al during preparation, indicating the progress in crystallization of the product. SEM-EDX analysis shows that the zeolite P produced contains Si/Al ratio of 2:1 with the formula of Na6Al6Si12O36.8H2O. The formation of zeolite was also confirm by FTIR absorption at 1040 cm-1 and 432 cm-1, the regions commonly observed in aluminosilicate due to Si-O and Al-O stretching and bending modes. Exchange capacity of Ce(III) and Ce(IV) in the zeolite increased with increased in temperature with highest loading obtained 75.4 and 170.0 mg/g, respectively. The existence of cerium in the zeolite was confirmed by EDX spectrum. The resulting cerium exchanged zeolites were used for As(V) sorption experiments. Sorption of As(V) by both modified zeolite occurred over a wide pH range, which was pH 1 – 11 for Ce4ZP and pH 3-10 for Ce3ZP with maximum sorption at about pH 4. The sorption capacities increased with increasing initial As(V) concentrations and followed the Langmuir model with maximum sorption capacities of 22.0 mg g-1 at 25°C and increased to 34.0 mg g-1 at 90°C. This is higher than the values for Ce3ZP which was 8.72 mg g-1 at 25°C and increased to 23.42 mg g-1 at 90°C, indicating that the As(V) sorption process is endothermic. The endothermic nature of sorption process was confirmed by the positive value of sorption enthalpy change, ΔH°. The free energy change, ΔG° for the sorption was negative showing that the sorption process is spontaneous. The increase in ΔS0 upon As(V) sorption could be partly due to the release of coordinated water molecules from Ce(IV) ion in the zeolite. Kinetic study showed that the As(V) sorption by Ce4ZP follows a second order kinetic model. The unmodified Zeolite P did not significantly remove As(V). This result infers that the active sorption site for As in the Zeolite was the cerium metal ion. In the acidic to natural pH range, sorption of arsenate ion was also followed by increase in pH of the solution from its initial value. The mechanism of sorption process could be a ligand exchange reaction with hydroxide ion on the surface of cerium ion and the formation of surface complexes between oxygen on the arsenate with the cerium metal ion on the zeolite. The selectivity study showed that the sorption of As(V) was affected by the presence of phosphate but not affected with bromide, chloride, nitrate, sulphate, carbonate and chromium. The Ce exchanged zeolite was found effective for the removal of arsenic in wastewater samples from wood treatment industries.